Вступ - Jenkovszky, Laszlo; Schicker, Rainer (Publishing house "Academperiodika", 2019)
Issues 7 and 8 of the Ukrainian Journal of Physics (V. 64, Nos. 7 and 8, 2019) contain original papers presented at the conference on New Trends in High-Energy Physics, organized by the BogolyubovInstitute for Theoretical Physics (BITP), National Academy of Sciences of Ukraine and held in Odessa on May 12–18, 2019, https://indico.bitp.kiev.ua/event/1/. The present issues are dedicated to the 110-th anniversary of great scientist M.M. Bogolyubov, founder and first director of BITP...